Choosing Wisely Brazil initiative for Women’s Health/Pelvic Floor Physical Therapy: study protocol - Driusso, Patricia (2022)
INTRODUCTION: The Choosing Wisely initiative aims to promote discussions among health professionals and patients to reduce low-value care that confers no benefit or can cause harm to health. OBJECTIVE: To describe the process for developing the Brazilian Choosing Wisely list for Women’s Health/Pelvic Floor Physical Therapy. METHODS: The research will be conducted in three stages. In the first stage, physical therapists with experience in women’s health/pelvic floor will be invited to compose a panel of experts and respond to a form. The Delphi method will be used to derive a list of evidence-based statements. In the second stage, members of the research team will review all the recommendations provided by the expert panel. In the third stage, a sample of physical therapists will vote on the previously selected statements. The recommendations with the most votes in the national survey will be submitted to Choosing Wisely Brazil, and a final list of recommendations will be published.